The Energy Union Tour – success or failure? - Pach-Gurgul, Agnieszka (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
The objective of the Energy Union is to integrate 28 national energy markets, guarantee free movement of energy through the borders of the member states, implement new technologies, increase energy efficiency and renew transmission infrastructure. This project is advocated in response to the energy crisis of 2009, between Russia and Ukraine, as a result of which the gas transit to some of the EU countries was discontinued. This project, however, does not enjoy equal interest among all EU member states. This is the outcome of the national interests of some member states, which, for many years, have had good political and economic relations with the Russian Federation, particularly in the area of energy raw materials. Therefore, Maroš Šefčovič – the European Commissioner in charge of the Energy Union, organised an Energy Union Tour, i.e. a series of meetings in all the member states, taking place at the turn of 2015–2016, the objective of which was to show what the Energy Union could offer each of them. The structure of the paper was determined by the research procedure and the response to all the research questions, comprising: introduction, reflections on the security of the energy raw material supply and the projects of Energy Union and Energy Union Tour as well as the conclusions from the research and the summary.

Założeniem Unii Energetycznej jest zintegrowanie 28 krajowych rynków energii, zagwarantowanie swobodnego przepływu energii przez granice państw członkowskich, wdrożenie nowych technologii, zwiększenie efektywności energetycznej oraz odnowienie infrastruktury przesyłowej. Jest to projekt promowany w odpowiedzi na kryzys energetyczny z 2009 r. pomiędzy Rosją a Ukrainą, w wyniku którego wstrzymano tranzyt gazu do niektórych krajów UE. Projekt ten nie cieszy się jednak zainteresowaniem wszystkich państw członkowskich UE w równym stopniu. Podyktowane jest to interesem narodowym niektórych państw członkowskich, które od lat posiadają z Federacją Rosyjską dobre relacje dotyczące sektora surowcowo-energetycznego. W związku z tym Maroš Šefčovič – komisarz ds. Unii Energetycznej, zorganizował tzw. Energy Union Tour – serię spotkań we wszystkich krajach członkowskich, odbywających się na przełomie 2015–2016 roku, pokazujących, co Unia Energetyczna może zaoferować dla każdego z nich. Struktura artykułu została podporządkowana procedurze badawczej oraz odpowiedzi na pytania badawcze i obejmuje: wprowadzenie, rozważania na temat bezpieczeństwa dostaw surowców energetycznych w UE, projektu Unii Energetycznej i Energy Union Tour oraz wnioski wynikające z przeprowadzonych spotkań i podsumowanie.
The Energy Union Tour – sukces czy porażka?
Keywords: Energy Union Tour; Energy Union; energy security; energy policy; internal energy market; polityka energetyczna UE; Energy Union Tour; Unia Energetyczna; bezpieczeństwo energetyczne UE; wewnętrzny rynek energii